2016
DOI: 10.5539/ibr.v9n7p64
|View full text |Cite
|
Sign up to set email alerts
|

Employee Participation in Decision-making (PDM) and Firm Performance

Abstract: <p>The objective of this study is to examine the influence of employee participation in decision-making on firm performance in Saudi Arabia’s manufacturing sector. Data were collected through pre-validated, piloted questionnaires, which were e-mailed to 341 manufacturing firms. The questionnaires asked about employee involvement in decision-making and performance variables. The response rate was 63.4 percent. Dimensions of PDM were rendered into 20 statements in the form of a five-point Likert scale. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…As such, their job performance will improve in line with the suggestion made by Hellriegel et al (1998). A study by Alsughayir (2016) found participation to be positively related to employees' performance.…”
Section: High Performance Work Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, their job performance will improve in line with the suggestion made by Hellriegel et al (1998). A study by Alsughayir (2016) found participation to be positively related to employees' performance.…”
Section: High Performance Work Practicesmentioning
confidence: 99%
“…According to them, these practices serve to motivate talents and are considered increasingly salient in enhancing the productivity of the health-care workforce in private hospitals. Therefore, in view of our preliminary findings and the need for parsimony, as well as in harmony with the approach taken by other researchers (Alsughayir, 2016;Leggat et al, 2011), we selected these three practices in predicting nurses' job performance through the mediating role of job satisfaction. A review of the literature on the role of these three HPWPs on job performance has been wellestablished as shown in the following section.…”
Section: High Performance Work Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying SMEs in Lagos state of Nigeria Ojokuku and Sajuyigbe (2014), find a robust positive significant relationship between employee participation in decision-making and organisational performance. In the same direction, Alsughayir (2016) using the regression analysis technique examine employee participation in decision-making in manufacturing companies in Saudi Arabia. The results show a significant and positive relationship between PDM and firm performance.…”
Section: Participatory Decision-making and Firm Performancementioning
confidence: 99%
“…Study on employee performance has been done by many researchers such as in the manufacturing industry [11][12][13][14][15][16]. A study conducted by Hanantoko and Nugraheni regarding the performance of employees in the manufacturing industry states that companies engaged in the manufacturing sector rely on the high quality and employee performance [13].…”
Section: Introductionmentioning
confidence: 99%